Real-time biomechanical biofeedback effects on top-level rifle shooters - Mullineaux, D. R.; Underwood, S. M.; Shapiro, R.; Hall, J. W. (Applied Ergonomics, 2012)
The aim was to examine the effects of training with real-time biomechanical biofeedback on technique and performance of rifle shooters. Top-level shooters were randomly assigned to biofeedback- (n = 5) and control- (n = 4) groups. Bi-weekly training of 20 shots air-rifle for 4 weeks, with pre- and post-tests of 20 shots air-rifle and smallbore, were performed. The biofeedback group received individualized real-time auditory biofeedback on postural- and barrel-stabilities. Results revealed a technique of reducing postural- and barrel-stabilities towards triggering (e.g. barrel speed 8.0 ± 1.2 mm/s at 3.0-1.0 s reducing to 5.4 ± 0.8 mm/s at 0.3-0.1 s). There were no changes pre- to post-tests and no differences between groups in these measures of stability. The biofeedback group showed meaningful improvements in performance measures, whereas the control group showed no improvement (e.g. smallbore shot group diameter change: biofeedback group -2.6 mm; control group 0.1 mm). Biomechanical biofeedback is proposed to have improved performance, possibly through training better decision making, but the actual cause requires further research.